Families of children with developmental disabilities understanding stress and opportunities for growth - Carroll, David W. 1950- (American Psychological Association, 2013)
On the other hand, parents often find meaning and benefit in their lives with children with disabilities. I believe that the characterization of the mix of emotions found here will be useful for clinicians who treat families of children with disabilities"--Preface. (PsycINFO Database Record (c) 2013 APA, all rights reserved)
Keywords: Disabled Children; Parents of children with disabilities / Services for; Children with disabilities / Family relationships; Family social work